How do the Customary Forest and Protected Forest Management Principles affect Ambon City Protected Forest Management between the Government and Indigenous Peoples? (Case in the Mount Sirimau Protection Forest Group, Ambon City, Maluku Province) - Ris Hadi Purwanto; Dwiko Budi Permadi; Evelin Parera; Sumardi (Jurnal Manajemen Hutan Tropika, 2022)
Protection forests are state forests that are authorized by the government to be managed, but on the other hand, indigenous peoples already exist and manage forests that are claimed as customary forest. How is the management of protection forests between the government and indigenous peoples? The purpose of this study is to examine the management of protection forests between the government and indigenous peoples and the collaboration in the management of protection forests between the two. The results showed that the management of protection forests by the government was not optimal at the site level based on the principles of protection forest management that had only been done with boundaries: only area boundaries, not blocks and plots, forest protection such as area patrols, installation of prohibition boards and appeals) and land rehabilitation (planting with woody plant species and multi-purpose trees. Protected forest management by indigenous peoples has touched the site level on several aspects of protected forest management principles. Protected management activities by indigenous peoples following the principles of protected forest management are the cultivation of fruit plants, land use with dusung/traditional agroforestry cropping patterns, forest protection is prohibited from cutting trees at water sources, along riverbanks, replanting if cutting fruit trees that are not productive, utilizing non-timber forest products. The government as the planner but implementing it in the field is the indigenous people who are accompanied by the government and joint monitoring and evaluation. Protected forest management based on the principle of protected forest management is more optimally carried out in a collaborative and complementary manner between the government and indigenous peoples.